THERAPEUTIC EFFICACY OF MODERN ANTIHELMINTHICS FOR TRICHOSTRONGYLOSIS OF GEESE - Starodub, Ye. (Scientific Progress & Innovations, 2021)
Expanding the range of poultry farming products is essential to improve the supply of high quality food. One of the sources of dietary types of these products is goose farming. Among the important factors influenc-ing the productive qualities, protective mechanisms of poultry, as well as the efficiency of the industry, is ensuring the veterinary welfare of poultry farms concerning parasitic diseases, including trichostrongylosis. The aim of the study was to establish the anthelminthic efficacy of preparations of different chemical groups in fighting trichostrongylosis of geese. Experimental testing of such anthelminthic preparations of domestic production was carried out: Fenzole 22 % (AS – fenbendazole), Brovadazole plus (AS – piperazine adip-inate, fenbendazole), Levamisole-80 (AS – levamisole hydrochloride), Univerm (AS – aversectin C), Pipera-zine 45 % (AS – piperazine adipinate). The main indicators of anthelmintic action were extensefficacy and intensefficacy. According to the results of coproovoscopical examination of geese in experimental and con-trol groups, it was found that the most effective anthelminthic preparations against goose trichostrongylosis were Brovadazole plus, Levamisole-80 and Univerm, where on the 14th day of the experiment extens- and intensefficacy reached 100 %. At the same time, Levamisole-80 and Univerm showed 100 % effectiveness on the 3rd day of the experiment, and the effectiveness of Brovadazole plus on the 3rd day was 75.0 and 71.55 %, respectively. Fenzole 22 % and Piperazine 45 % were less effective in treatment of goose trichostrongylosis. Indicators of extense- and intensefficacy of Fenzole 22 % on the 3rd day of the experiment were 25 and 71.55 %, respectively, on the 7th day – 75 and 76.39 %, on the 14th day – 75 and 83.35 %. The effectiveness of Piperazine 45% on the 3rd day of the experiment was 12.5 and 60.99 % respectively, on the 7th day – 37.5 and 63.95 %, on the 14th day – 62.5 and 77.4 %, which indicates insufficient anthelminthic effect of this drug. The obtained data allow us to recommend Brovadazole plus, Levamisole-80 and Univerm preparations for effective control and prevention of goose trichostrongylosis.